Brain Volumes and Developmental Outcome in Childhood Following Fetal Growth Restriction Leading to Very Preterm Birth - Morsing, Eva; Malova, Mariya; Kahn, Anna; Lätt, Jimmy; Björkman-Burtscher, Isabella M.; Maršál, Karel; Ley, David (Frontiers in Physiology, 2018)
Background: Children born very preterm (PT) after fetal growth restriction (FGR) exhibit cognitive impairment at early school age. The relationship between neurodevelopmental impairment and attained regional brain volumes is unknown. Methods: We studied 23 preterm children with FGR (PT-FGR), 24 matched preterm children appropriate for gestational age (PT-AGA), and 27 matched term AGA children (T-AGA) by measuring brain volumes with magnetic resonance imaging at early school age. Cognitive and motor functions were assessed by the Wechsler Intelligence Scales for Children and the ABC-Movement score. Results: The mean (SD) full-scale IQ was 80 (17) in the PT-FGR group and 103 (12) in the PT-AGA group (p<0.001). The PT-FGR group had lower mean total, grey matter, white matter, thalamic, cerebellar white matter and hippocampal volumes as compared to the T-AGA group (p=0.01, 0.04, 0.003, 0.002, 0.001 and 0.009, respectively). Brain volumes did not differ significantly between the PT groups. Reduction of hippocampal volume correlated with degree of growth restriction at birth (r=0.46, p=0.05). Neither the full-scale IQ nor the ABC movement score <5th percentile were related to brain volumes. Conclusions: Brain volumes as determined by MRI at early school age were primarily associated with degree of prematurity at birth and less with FGR. Regional brain volumes did not discriminate cognitive and motor function beyond that predicted by gestational age at birth.